Beneficial reuse of dam fine sediments as clinker raw material. (10th September 2019) - Faure, A.; Coudray, C.; Anger, B.; Moulin, I.; Colina, H.; Izoret, L.; Théry, F.; Smith, A.
Highlights: 7 dam sediments from different French regions are suitable for clinker production. Clinkers produced using 10–15% of sediment are similar to industrial ones. Special features (polymorphisms and phase ratios) can be induced by sediments. Key-criteria: Grain size, silica ratio and minor elements (Mg, Na, K) in sediments composition. Abstract: The accumulation of fine sediments (<200 µm) occurs in hydroelectric dams due to watershed erosion and solid transport. A rigorous and sustainable sediment management is required. Although most of these materials are transferred into the watercourse downstream, a significant quantity might have to be managed as on-land waste in the future. Considering that sediments contain silica, alumina, calcia and iron oxide as main chemical constituents, they could be useful candidate raw materials in the cement industry for the manufacture of clinker. This work concerns sediments from French dams. Whatever their origin, each sediment is suitable for a beneficial reuse as silico-aluminous raw material for clinker production. The characteristics of the raw sediments can lead to specific microstructures in the clinkers. However, clinker characteristics can still be controlled by adjusting raw mix proportions, maintaining a rather high sediment content in the mix (between 10 and 15 wt%).